2018
DOI: 10.1002/ijc.31976
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a validated methylation triage signature for human papillomavirus positive women in the HPV FOCAL cervical cancer screening trial

Abstract: Human papillomavirus (HPV)‐based cervical cancer screening requires triage of HPV positive women to identify those at risk of cervical intraepithelial neoplasia grade 2 (CIN2) or worse. We conducted a blinded case–control study within the HPV FOCAL randomized cervical cancer screening trial of women aged 25–65 to examine whether baseline methylation testing using the S5 classifier provided triage performance similar to an algorithm relying on cytology and HPV genotyping. Groups were randomly selected from wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
82
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(98 citation statements)
references
References 38 publications
(81 reference statements)
10
82
2
Order By: Relevance
“…This is the first study to report levels of methylation of HPV 16 genes and EPB41L3 measured in tumors of OPC cases and oral gargle specimens from cases and controls with sufficient effect size and attributable fraction as to suggest a primary epigenetic association, a reasonable assumption given that to date no meaningful predisposing mutations have been found that may account for a majority of OPC cases. In prior studies of the cervix and anal canal methylation of HPV 16 genes and EPB41L3 were significantly positively associated with increasing grade of disease and methylation levels increased with time of progression to cancer . In our study, we report three important observations: ( i ) among OPC cases, methylation levels detected in the oral gargle and tumors were correlated, indicating that the measurement of these biomarkers in the oral gargle is representative of the tumor; ( ii ) HPV 16 methylation (L1, L2 and E2 genes) was predominantly observed among OPC cases and not detectable among disease‐free men who were oral HPV 16 positive, except for methylation of E2 in one HPV 16 positive control; ( iii ) oral EPB41L3 methylation combined with HPV 16 gene methylation status had good sensitivity and high specificity for the detection of OPC.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…This is the first study to report levels of methylation of HPV 16 genes and EPB41L3 measured in tumors of OPC cases and oral gargle specimens from cases and controls with sufficient effect size and attributable fraction as to suggest a primary epigenetic association, a reasonable assumption given that to date no meaningful predisposing mutations have been found that may account for a majority of OPC cases. In prior studies of the cervix and anal canal methylation of HPV 16 genes and EPB41L3 were significantly positively associated with increasing grade of disease and methylation levels increased with time of progression to cancer . In our study, we report three important observations: ( i ) among OPC cases, methylation levels detected in the oral gargle and tumors were correlated, indicating that the measurement of these biomarkers in the oral gargle is representative of the tumor; ( ii ) HPV 16 methylation (L1, L2 and E2 genes) was predominantly observed among OPC cases and not detectable among disease‐free men who were oral HPV 16 positive, except for methylation of E2 in one HPV 16 positive control; ( iii ) oral EPB41L3 methylation combined with HPV 16 gene methylation status had good sensitivity and high specificity for the detection of OPC.…”
Section: Discussionsupporting
confidence: 60%
“…In prior studies of the cervix 53 and anal canal 54 methylation of HPV 16 genes and EPB41L3 were significantly positively associated with increasing grade of disease and methylation levels increased with time of progression to cancer. 55 In our study, we report three important observations: (i) among OPC cases, methylation levels detected in the oral gargle and tumors were correlated, indicating that the measurement of these biomarkers in the oral gargle is representative of the tumor; (ii) HPV 16 methylation (L1, L2 and E2 genes) was predominantly observed among OPC cases and not detectable among disease-free men who were oral HPV 16 positive, except for methylation of E2 in one HPV 16 positive control; (iii) oral EPB41L3 methylation combined with HPV 16 gene methylation status had good sensitivity and high specificity for the detection of OPC. Oral gargle HPV 16 L1 and E2 methylation in p16 positive cases was observed although HPV 16 L2 methylation was not detected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies of S5 performance [20], the sensitivity for cancer at the suggested triage cutoff of 0.8 was 100%. In our study, the results showed that even at a cutoff of 2.85, all cancers were detected.…”
Section: Discussionmentioning
confidence: 91%
“…However, the S5®(careLYFE) methylation tests for the triage of cervical cancer and "≥HSIL+" among Chinese women remain elucidated. The S5 assay was developed in a colposcopy study and has been well tested in the UK, Canada, and Mexico [19][20][21][22]. As the infection rates of HPV31 and HPV33 in China are low, as well as the lower infection rates of HPV31 and HPV33 in HSIL and cancer, Care Me is a methylation classifier consisting of three regions: EPB41L3, HPV16, and HPV18.…”
mentioning
confidence: 99%